Building and Blocking: The Two Faces of Technology Acquisition - Christoph Grimpe; Katrin Hussinger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
Gaining access to technological assets and patents, in particular, has long been a major motive and objective for firm acquisitions. On the one hand, patents are used as a building instrument for the acquirer's technology portfolio. On the other hand, patents can be attractive because of their strategic value as a bargaining chip, e.g. in licensing negotiations. This is especially the case if patents have the potential to block competitors. Drawing on transaction cost economics and the resource-based view of the firm, we analyze the importance of these two faces of technology acquisition for the valuation of a target firm. Empirical evidence for European firm acquisitions in the period from 1996 to 2003 indicates that the price paid by an acquirer for a target increases with the building and blocking potential of the target's patents, especially if building and blocking patents are in technology fields related to the acquiring firm's patent portfolio. Our results have implications for the technology strategy of the firm, in that M&A transactions may considerably impact technology markets, increasing the concentration of key technologies.
Older version: http://hdl.handle.net/10419/24738
Keywords: G34; L20; O34; 330; Firm acquisitions; technology; building patents; blocking patents; Übernahme; Wissenstransfer; Patent; Wettbewerbsbeschränkung; Unternehmenswert; Technologie; EU-Staaten